Ruins and Rivals : The Making of Southwest Archaeology - Snead, James E. (James Elliott), 1962- (Book collections on Project MUSE., 2003)
"Tracing the historical development of archaeology in the Southwest from the 1890s to the 1920s and its relationship with the popular conception of the region, James Snead shows how the decades-long competition between institutions and their advocates ultimately created an agenda for Southwest archaeology that has survived into modern times." --Book Jacket.